1988
DOI: 10.2307/1242068
|View full text |Cite
|
Sign up to set email alerts
|

Market Distortions and Benefits from Research

Abstract: The benefits from cost‐reducing research and their distribution under a range of price policies are compared with those that would arise in the absence of the policies. While any price policy affects the distribution of research benefits, the net national or world benefits may be reduced, lef unchanged, or increased, depending on the nature of the policy and the significance of the country in the world market for the commodity. Some implications for decisions on price policies and for distortions in incentives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 1 publication
4
47
0
Order By: Relevance
“…Globally it would be virtually no different, for reasons explained in Alston, Edwards and Freebairn (1988) and Anderson and Nielsen (2004). But the gains to developing countries in the absence of distortionary cotton policies would be slightly greater (12 percent so in the case of Sub-Saharan Africa), while those to high-income countries would be less (middle columns of Table 6).…”
Section: What If Cotton Subsidies and Tariffs Were Removed?mentioning
confidence: 98%
“…Globally it would be virtually no different, for reasons explained in Alston, Edwards and Freebairn (1988) and Anderson and Nielsen (2004). But the gains to developing countries in the absence of distortionary cotton policies would be slightly greater (12 percent so in the case of Sub-Saharan Africa), while those to high-income countries would be less (middle columns of Table 6).…”
Section: What If Cotton Subsidies and Tariffs Were Removed?mentioning
confidence: 98%
“…Where simple price weights are used to aggregate inputs, the TFP index will not reflect these gains either. 31The complex issues of how to deal with policy-induced distortions has attracted considerable recent attention (Norton et al, 1987;Alston et al, 1988;and Oehmke, 1987) but this literature provides no easy answers for a case like this. 321t should be added that the model does not work at all in first differences.…”
Section: C O N C L U S I O N Smentioning
confidence: 99%
“…inputs at their market prices, whereas the social rate of return to research should be evaluated at social opportunity costs, to account for the income transfers caused by distortions in product and input markets.The impact on returns to research of a single distortion in product markets has been demonstrated by Oehmke (1988) and by Alston et al (1988); in this paper we generalize their results to capture the multiple distortions which characterize most developing countries. But these estimates may be incorrect if, as is often the case, market prices are distorted by market failures or government policies and hence do not reflect social values.…”
mentioning
confidence: 55%
“…The impact on returns to research of a single distortion in product markets has been demonstrated by Oehmke (1988) and by Alston et al (1988); in this paper we generalize their results to capture the multiple distortions which characterize most developing countries. In particular, we consider both commodity-specific policies affect-0169-5150/95/$09.50 © 1995 Elsevier Science B.V. All rights reserved …”
mentioning
confidence: 55%